Conocimientos y actitudes acerca de la estimulación temprana en padres de familia de la Institución Educativa Inicial N° 397 Corazón de Jesús, Iquitos 2021 - Rios Gutiérrez, Angie Solange (2025)
The study had as general objective, to determine the level of knowledge and attitudes about early stimulation in parents of the Institution Cuna-Jardín 397 "Corazón de Jesús". The type of study was non-experimental, with a simple descriptive design and a cross-sectional approach. The sample of the study consisted of 96 parents of both sexes of the educational institution; for the collection of data, a questionnaire survey was used as an instrument to measure the level of knowledge and a Likert-type scale to collect attitude information. As a result, it was found that the majority of parents regarding early stimulation are at a Low level with 80%; followed by the medium level with 18% and finally with 2%. Arriving as a conclusion; parents have limitations in knowledge and attitude about early stimulation, from this it can be inferred that parents do not stimulate their children.